Diagnosis and proposal of erosion control downstream of the Park Alfredo Werner Nyffeler, in Maringá - Paraná - Valim, Fernanda Assunção; Orioli, Monigleicia Alcalde; Freire, Cipriano José de Azevedo; Pompeu, Cássia Rocha; Okawa, Cristhiane Michiko Passos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
The surface runoff role in the urban erosion in Northwest Paraná cities was strengthened by many factors, such as the establishment of the cities often in disaggregated soil areas, vegetation cover removal, soil surface impermeabilization caused by construction and poorly executed embankment areas. In Maringá, Paraná, in a bottom valley located near the park Alfredo Werner Nyffeler, there is an accelerated erosive process, damaging half of the urban drainage pipes, which are located around one meter far from the sidewalk. In that way, it poses a risk to the local population and may lead to a collapse of the drainage structure. Within this context, this work aims to diagnose and identify the possible aspects that caused these issues and to design a gabion wall to stem the significative erosive process occurring in the area. Thus, on-site data survey and laboratory analysis were carried out in order to characterize the soil and, by means of the software GawacWin, a gabion retaining wall in order to use it as a prompt, needed retaining measure was designed. The obtained results showed a lack of awareness by the local population in regard to the solid waste deposition, which accumulates downstream of the park. In addition, the drainage pipes could not cope with the peak flows, causing structural damage, leaks and uncovering the junction box. A silty clay embankment was found in the area, which is an expansive soil, contaminated with rubble and the soil compaction was not properly executed. It was used to level the area for the pipeline passage, contributing to the erosion. A gabion wall, with 6m high and 3m base, showed to be an efficient solution with regard to terrain loads. Furthermore, the price, simple construction and the easy merging with the environment are advantages for the gabion wall, when compared to other structural measures.